2015
DOI: 10.1111/jgs.13314
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Comorbidity Burden and Rapid Cognitive Decline in Individuals with Mild to Moderate Alzheimer's Disease

Abstract: Comorbidity burden was associated with rapid cognitive decline in subjects with AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 26 publications
2
32
0
2
Order By: Relevance
“…Adjustment for baseline age was unclear in two studies [15, 19]. Adjustment for education was lacking or unclear in five studies examining cognition [16, 17, 1921]. Adjustment for baseline symptoms of interest was unclear in one out of six longitudinal studies [19].…”
Section: Resultsmentioning
confidence: 99%
“…Adjustment for baseline age was unclear in two studies [15, 19]. Adjustment for education was lacking or unclear in five studies examining cognition [16, 17, 1921]. Adjustment for baseline symptoms of interest was unclear in one out of six longitudinal studies [19].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the majority of AD cases frequently suffer from multiple complications (e.g., DM, other neurodegenerative disorders, cardiovascular diseases, and renal diseases). These comorbidities can enhance the complexity that underlies AD pathogenesis [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The link between cognitive decline and physical comorbidities in AD has been substantially reported so far [11–14]. People with more comorbidities had more rapid deterioration in cognition and also showed significantly faster decline in daily functioning [15–17]. It has been shown that the effect of physical activity and exercise might be effective on cognitive function [18] and thus the decline in daily functioning due to cognitive deterioration could raise physical comorbidities in older subjects.…”
Section: Discussionmentioning
confidence: 93%